The Role of Nicotine in the Corrosive Behavior of a Ti‐6Al‐4V Dental Implant. (26th July 2014) - Royhman, Dmitry; Dominguez‐Benetton, Xochitl; Yuan, Judy Chia‐Chun; Shokuhfar, Tolou; Takoudis, Christos; Mathew, Mathew T.; Sukotjo, Cortino
Abstract: Background: Metals react chemically/electrochemically in electrolytic solutions, such as that present in the oral cavity, which leads to corrosion of metal dental implants. Corrosion can increase the failure rate of dental implants. Purpose: This study evaluated the corrosion behavior of nicotine on Ti‐6Al‐4V under physiological conditions. It was hypothesized that nicotine in artificial saliva would have an adverse effect on the corrosion of Ti‐6Al‐4V. Methods: Ti‐6Al‐4V discs were electrochemically analyzed using a three‐electrode electrochemical cell. The disks were immersed in an electrolytic artificial saliva with varying pH (3.0 and 6.5) and nicotine concentration (control, 1 mg/mL, 5 mg/mL, and 20 mg/mL). Open circuit potential, cyclic polarization, and electrochemical impedance spectroscopy (EIS) tests were conducted. Results: Electrochemical parameters indicated that the presence of nicotine significantly reduced ( p  < .05) the corrosion rate. For example, there was a decrease in corrosion current density from 2.94 × 10 −3  μA/cm 2 to 1.43 × 10 −3  μA/cm 2 in control compared with 20 mg/mL nicotine at pH 6.5. EIS results exhibited an unexpected trend in that the presence of nicotine decreased polarization resistance. This suggested a decrease in passive film growth. Conclusions: At certain concentrations, nicotine inhibits local corrosion; however, it also prevents the formation of a protective oxide film.